Pengaruh Kompensasi, Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Pegawai Pada Badan Kepegawaian Pendidikan Dan Pelatihan Kabupaten Kutai Timur - Nurliah Desi Parante; Rina Rina; Andi Hendra Syam (STIM-LPI Makassar, 2022)
The purpose of this study was to determine the effect of compensation, work discipline and work environment on employee performance at the Education and Training Personnel Board of East Kutai Regency. The population in this study were employees at the Education and Training Personnel Board of East Kutai Regency with a total sample of 32 people. The methods of collecting data in this study are questionnaires, interviews, and documentation. Methods of data analysis using descriptive methods and quantitative methods, namely with multiple linear regression analysis used to measure the effect of compensation, work discipline and work environment on employee performance at the East Kutai Regency Personnel Education and Training Agency. Based on the independent variable F test (compensation, work discipline and work environment) together have a positive and significant influence on the dependent variable (employee performance). Through testing the correlation coefficient (R) it is found that the level of correlation or relationship between compensation, work discipline and work environment on employee performance is a high relationship, namely 59.4%. And compensation is the most dominant factor influencing employee performance at the East Kutai Education and Training Personnel Board